Design and construction of a Stirling engine prototype - Scollo, Leonardo (2008)
In this work an external combustion engine is presented, which was designed through principles of energetic similarity and scaling, combined with adiabatic simulation, pressure loss and heat exchange characteristics analysis. These type of engines have the great advantage of having the heat source applied from outside, therefore resulting in very versatile machines which can be utilized with hydrogen, concentrated solar energy, biomass or fossil fuels. Details of the construction carried out mostly with conventional machine parts produced in Argentina are given. Finally, the results of the preliminary tests with the constructed prototype are shown.